The sanctity of the county in Irish public life: here to stay or passed its 'sell-by' date?. Issue 4 (2nd October 2018) - Callanan, Mark
ABSTRACT: The county as the main source of local identity has a key influence on public life in the Republic of Ireland, and amongst other things is reflected in Dáil constituencies, vote transfer patterns, and as the basis for local government. Previous proposals around territorial reform and recent experience with attempted reconfigurations of the county structure (and in particular reviews of county boundaries) suggest that the county is one of those aspects of Irish political life that is highly resistant to change. Contemporary and future debates over public service reform and consolidation, as well as over urbanisation, metropolitan governance and the economic importance of 'city regions' will perhaps frame the next phase of debate over the future of the county. However, based on past and more recent proposals for local government reform and boundary change, any future proposals for territorial restructuring are likely to be mediated by a requirement to respect traditional county loyalties. Planning reforms and efforts to place a greater focus on urban-led growth may be challenged by the status of the county as a central and enduring source of identity for most Irish citizens.